AN EXAMINATION OF HOW EMPLOYEE PERFORMANCE AT KEMENDIKBUDRISTEK IS IMPACTED BY LEADERSHIP STYLE, WORK ENVIRONMENT, MOTIVATION, AND CAREER DEVELOPMENT - Setiasih; Ida Adhani; Madin Syauly (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
The aim of the test is to insure the effect of leadership style partially or simultaneously, work environment, motivation, and employee development on employee performance at Kemendikbudristek. Questionnaires are sent as part of a combined procedure used in this study to collect data. The sample consisted of 95 employees of the Kemendikbudristek, utilizing the Slovin equation with a 5% error rate (e). Analysis of multiple linear regression is the analysis of data technique employed, in addition to t, F, as well as assessments of coefficients of determination. The equation Y = the determination coefficient value obtained, which is the coefficient of determination of the employee performance variable that the variable explains, is the result of the analysis of multivariate linear regression. It is anticipated that this study will examine how Kemendikbudristek employees perform in relation to leadership style, work environment, motivation, and career growth.